Paraoxonase (PON1) activities and lipid profiles among organophosphates (OPs) pesticide exposed workers - Ishaka, Aminu; Abdullah, Nor Zamzila; Mohamed, Rozilah @ Abdul Hadi; Samsuddin, Niza; Mohd Rus, Razman (2010)
Paraoxonase (PON1) is a high density lipoprotein (HDL) associated enzyme that is known for its function to hydrolyze organophosphate (OPs) into a relatively harmless substance and prevent atherosclerosis by inhibiting oxidative modification of low density lipoprotein (LDL). In some studies low PON1 activity was reported among individuals who are exposed to OPs, while in different studies low PON1 activity was associated with a high risk of coronary artery disease (CAD). However, the link between OPs exposure and lipid profiles which are known risk factors of CAD has not yet been reported. The aim of our present preliminary study was to compare the activities of PON1 and lipid profiles between the workers who are exposed to OPs and the comparative non-exposed group. This cross sectional comparative study was carried out on a total of 105 subjects comprising of 53 OPs exposed group and 52 comparative non-exposed group. Fasting serum samples were analyzed for PON1 activities towards substrates paraoxon, phenylacetate and diazoxon as well as for total cholesterol, triglycerides, HDL-C and LDL-C. The results showed a significantly lower diazoxonase activity (p<0.05) among the OPs exposed group, but the lipid profiles were not significantly different (p>0.05) between the two groups. Our study suggested that the decreased PON1 activity among OPs exposed individuals cannot be linked to the atherosclerosis and CAD through the lipid profiles. A larger scale study is required to confirm our observation.